If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -3(a + 5) = -10 Reorder the terms: 2 + -3(5 + a) = -10 2 + (5 * -3 + a * -3) = -10 2 + (-15 + -3a) = -10 Combine like terms: 2 + -15 = -13 -13 + -3a = -10 Solving -13 + -3a = -10 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + -3a = -10 + 13 Combine like terms: -13 + 13 = 0 0 + -3a = -10 + 13 -3a = -10 + 13 Combine like terms: -10 + 13 = 3 -3a = 3 Divide each side by '-3'. a = -1 Simplifying a = -1
| 9x=4x+288 | | 4x^2+x-2= | | 8x+5(3x-14)=-1 | | q=12-5p | | 2/3(7/8+2x)-3/8=5/8 | | (1/3)-x=(3x/2)-1 | | H+2/5=7/10 | | t=-6(3)+19 | | x/3=6/2 | | 7x^2+4x+84=0 | | 1/3*72 | | -8x+2(-6x+19)=-22 | | x/9=5/3 | | 8+6m-4=6m+22-2m | | 1/3x-x=3x/2-1 | | 0.75x+.05(18-x)=.10(23) | | y+3y+12=28 | | 5x-2x=7x | | y+4y+12=28 | | 2x+1.2=8.9 | | 0.08(24)+0.02x=0.04(24+x) | | -1(4a-3b)= | | 8x+5y=3080 | | 7+ax=17-bx | | y=-3(4)+16 | | 3a+15=2(a-5) | | 18a^3-48a^2b+3a^3b-8ab^2= | | (16y^7/8y^3)^-2 | | -3(x-4)+15=-12 | | 30=5/2y | | 3x+17=-2x+12 | | k/4-3/4=10 |